Triglyceride-glucose index is associated with quantitative flow ratio in patients with acute ST-elevation myocardial infarction after percutaneous coronary intervention - Bingyan Yu; Bingyan Yu; Yuhao Mo; Xiangming Hu; Weimian Wang; Jieliang Liu; Junguo Jin; Ziheng Lun; Ci Ren Luo Bu; Haojian Dong; Yingling Zhou; Yingling Zhou (Frontiers in Cardiovascular Medicine, 2022)
BackgroundThe triglyceride-glucose (TyG) index is a novel marker representing the degree of insulin resistance (IR) and is closely related to cardiovascular diseases. However, the association between the TyG index and vascular function in patients with acute ST-elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI) remains unknown.Materials and methodsThis study was a post hoc analysis of a multicenter, prospective cohort study. In this study, patients with STEMI who underwent PCI were included, and coronary angiography data were analyzed by Quantitative coronary angiography (QCA) and quantitative flow ratio (QFR). In addition, the TyG index was calculated as follows: Ln [fasting triglyceride (mg/dl) × fasting blood glucose (mg/dl) × 1/2]. According to the post-PCI QFR, patients were divided into two groups: post-PCI QFR ≤ 0.92 group and post-PCI QFR > 0.92 group. Construction of logistic regression model to explore the relationship between the TyG index and post-PCI QFR.ResultsA total of 241 STEMI patients were included in this study. Compared with patients in the post-PCI QFR > 0.92 group, the TyG index was higher in the post-PCI QFR ≤ 0.92 group. Logistic regression model showed that after adjusting for other confounding factors, the TyG index was positively correlated with the risk of post-PCI QFR ≤ 0.92 (OR = 1.697, 95% CI 1.171–2.460, P = 0.005). Restricted cubic splines showed the cutoff value of TyG index associated with post-PCI QFR ≤ 0.92 risk was 9.75.ConclusionThe TyG index was associated with the risk of post-PCI QFR ≤ 0.92 in STEMI patients. The risk of post-PCI QFR ≤ 0.92 increased when the TyG index exceeded 9.75.